New campus-Family and Food Sciences building-0013
The Lone Three story structure on campus, Art-Home Economics Building, is expected to be ready for occupancy during the fall semester,1958. Students who plan for professions or avocations such as painters, docorators, illustrators, display artists and teachers may complete a four-year course in art. Home Econimics also offers training for teaching and various avocations----agricultural extension specialist, food service administrator and other positions.